M.A. SELIMOV: CONTRIBUTION TO THE DEVELOPMENT OF ISSUES OF PREVENTION OF RABIES, PERSONALITY AS A SCIENTIST AND PERSON (ON THE 100TH ANNIVERSARY OF THE BIRTH, 1918-2001) - A. D. Botvinkin; E. M. Mikhailovsky (Вопросы вирусологии, 2018)
.